Advances in the treatment of RET-fusion-positive lung cancer. (June 2021) - Pall, Georg; Gautschi, Oliver
Highlights: RET-fusions define a clinically relevant subgroup of NSCLC-patients. Selective RET-inhibitors show high efficacy and favourable toxicity. Acquired resistance can be considered the most prominent challenge in the future. Abstract: Ten years ago, RET-fusions were discovered as oncogenic drivers and potential drug targets in approximately 1% of metastatic lung adenocarcinomas. Several multikinase inhibitors were tested in clinical trials, however, their antitumor activity was limited. Recently, two selective and potent RET-inhibitors were approved for the treatment of patients with metastatic RET-fusion-positive lung cancer (RET-NSCLC). Here, we discuss the two RET-inhibitors selpercatinib and pralsetinib, and the management of patients with RET-fusion positive NSCLC.